Bio-inspired construction of melanin-like polydopamine-coated CeO2 as a high-performance visible-light-driven photocatalyst for hydrogen production. (28th August 2020) - Sridharan, M.; Kamaraj, P.; Vennila, R.; Huh, Yun Suk; Arthanareeswari, M.
Abstract : In recent years, cerium oxide has been the most widely studied photocatalyst due to its unique properties. Abstract : In recent years, cerium oxide has been the most widely studied photocatalyst due to its unique properties. However, bare CeO2 shows poor photocatalytic performance under visible-light irradiation because it absorbs only UV light that leads to fast recombination of photogenerated electron–hole pairs. Therefore, surface modification can be one of the effective strategies to improve the visible-light absorption and reduce the recombination rate of photogenerated charge carriers. Herein, a series of CeO2 /polydopamine (CeO2 @PDA) composites were successfully fabricated by the polymerization of dopamine on the surface of CeO2 . Our results demonstrated that the surface modification of CeO2 by a small amount of PDA could effectively inhibit the photocatalytic reaction; this not only promoted the photoelectron injection and reduced the charge recombination rate, but also controlled the overgrowth of Pt cocatalyst. As compared to bare CeO2, CeO2 @PDA shows remarkable photocatalytic hydrogen production performance. This composite also presents good durability and stability for the photocatalytic hydrogen production reaction. Thus, this study provides a new insight into the preparation of CeO2 composites with effective solar energy conversion.